Atatürk Dönemi Dış Politikasında Barış İlkesinin Uygulanmasına Bir Örnek: İspanya İç Savaşı - Gültekin K. BİRLİK (Gazi Akademik Bakış)
Although many European countries took sides during the Spanish Civil War, Turkey adopted the policy of “non-intervention”. In this context, Turkey forbid selling weapons to the parties in the Civil War and the Turkish civilains to join the war. Although Turkey was negatively affected by the Civil War particularly in terms of domestic and foreign politics, she demanded that the Civil War should be settled down through peaceful ways in accordance with her policy of “peace at home peace in the world”. Although the Civil War progressed against the Republicans, Turkey officially recognised the elected government of The Republicans during the Civil War. Only after the Civil War ended and it was recognised internationally, Turkey recognised the Nationalist government and sent diplomatic representative, which was a mutual act. As part of this policy, Turkey was closely concerned with the humanitarian side of the Civil War. In case of the most serious issue of the Civil War, that is the refugees, she decided to solve the problem of the Spanish Nationalist refugees in Madrid that took refuge in Turkey in line with her political tradition and took steps in the direction of bringing them to Turkey in 1937. In 1938, when the Republican Government interfered with the Spanish Nationalist Refugees that took refuge in Turkey, she showed numerous reactions. Although Turkey officially recognised the elected Republican Government, during the Civil War, when needed, she offered humanitarian help to both the Nationalist and the Republican sides. Although the Turkish media supported both sides, in line with Turkish foreign policy, it defended the idea that the Spanish domestic affairs should not be interfered with, the process of solution should be left to the Spanish people themselves and the problem should be solved peacefully.